(untitled) (Hoboken, N.J., 2006)
This volume applies multiple levels of analysis to neurobiological developmental organization, and functioning in normality and psychopathology. It also covers topics central to a developmental perspective on neuroscience.
Keywords: Mental illness,Developmental psychology,Developmental Disabilities,Bệnh tâm thần,Sự phát triển tâm lý,Sự rối loạn phát triển ( Tâm thần ); Etiology,Bệnh nguyên